Comparison of Continuous Proximal Versus Distal Adductor Canal Blocks for Total Knee Arthroplasty: A Randomized, Double-Blind, Noninferiority Trial. Issue 1 (January 2018) - Meier, Adam W.; Auyong, David B.; Yuan, Stanley C.; Lin, Shin-E; Flaherty, James M.; Hanson, Neil A.
Abstract : Background and Objectives: Adductor canal blocks (ACBs) are associated with improved analgesia, preserved quadriceps strength, and decreased length of hospitalization after total knee arthroplasty (TKA). However, controversy remains regarding the ideal location of a continuous block within the adductor canal, and it remains unclear whether similar clinical benefits are obtained irrespective of block location. In this randomized, double-blind, noninferiority study, we hypothesized that a continuous proximal ACB provides postoperative analgesia that is no worse than a continuous distal ACB. Methods: Subjects presenting for unilateral TKA were randomized in a 1:1 ratio to either a continuous proximal or distal ACB group. The primary outcome of this noninferiority study was opioid consumption within the first 24 hours following surgery. Secondary outcomes included quadriceps strength, pain scores, distance ambulated, and patient satisfaction. Results: Seventy-three subjects, 36 from the proximal group and 37 from the distal group, completed the study per protocol. The intention-to-treat analysis demonstrated a cumulative mean intravenous morphine equivalent consumption difference between the proximal and distal groups of −7.2 mg (95% confidence interval, −14.8 to 0.4; P < 0.001), demonstrating noninferiority of the proximal approach. The per-protocol analysis yielded similar results: −6.2 mg (95% confidence interval, −14.1 to 1.6; P < 0.001). No secondary outcomes showed statistically significant differences between the proximal and distal groups. Conclusions: This study demonstrates that a continuous proximal ACB offers noninferior postoperative analgesia compared with a distal continuous ACB in the first 24 hours after TKA. Clinical Trial Registration: ClinicalTrials.gov (NCT02701114).